Microfluidic-mediated nano-drug delivery systems: from fundamentals to fabrication for advanced therapeutic applications. Issue 29 (22nd May 2020) - Ma, Qingming; Cao, Jie; Gao, Yang; Han, Shangcong; Liang, Yan; Zhang, Tingting; Wang, Xinyu; Sun, Yong
Abstract : Microfluidics-mediated NDDS show uniform morphology, size and size distribution, reduced batch-to-batch variations and controllable drug delivering capacity. Abstract : Nano-drug delivery systems (NDDS) are functional drug-loaded nanocarriers extensively applied in the healthcare and pharmaceutical areas. Recently, microfluidics has been demonstrated as one of the most promising techniques to fabricate high-performance NDDS with uniform morphology, size and size distribution, reduced batch-to-batch variations and controllable drug delivering capacity. Here, a brief review of the microfluidic-mediated NDDS is presented. The fundamentals of microfluidics are first interpreted with an emphasis on the fluid characteristics, design and materials for microfluidic devices. Then a comprehensive and in-depth depiction of the microfluidic-mediated fabrications of controllable NDDS with well-tailored internal structures and integrated functions for controlled encapsulation and drug release are categorized and reviewed, with particular descriptions about the underlying formation mechanisms. Afterwards, recently appreciated representative applications of the microfluidic-mediated NDDS for delivering multiple drugs are systematically summarized. Finally, conclusions and perspectives on further advancing the microfluidic-mediated NDDS toward more powerful and versatile platforms for therapeutic applications are discussed.